Procyclical and countercyclical fiscal policies in non-euro EU member countries - Aurel Iancu; Dan Olteanu (Romanian Academy, National Institute for Economic Research, 2022)
The aim of this study is to determine the nature of the discretionary fiscal policy practiced by non-euro EU member states, namely to deduce some bias for one of the two types of fiscal policies - procyclical or countercyclical. For this purpose, we used time series for the period 1995-2020, of the cyclically-adjusted primary balance, the output gap, as well as additional indicators - public debt, fiscal rules index and election years. From the signs and magnitude of the correlation and regression coefficients, it results that almost all countries have learned the necessary lessons from the economic / financial crisis, in order to move from a procyclical policy, during 1995-2008, to an countercyclical policy, in 2009-2020.
Keywords: H61; H62; E62; E65; E32; 330; discretionary fiscal policy; fiscal reaction function; procyclicality; countercyclicality; economic cycle